Neural responses to social evaluative threat in the absence of negative investigator feedback and provoked performance failures. Issue 8 (20th January 2020) - Fehlner, Phöbe; Bilek, Edda; Harneit, Anais; Böhringer, Andreas; Moessnang, Carolin; Meyer‐Lindenberg, Andreas; Tost, Heike
Abstract: Functional neuroimaging of social stress induction has considerably furthered our understanding of the neural risk architecture of stress‐related mental disorders. However, broad application of existing neuroimaging stress paradigms is challenging, among others due to the relatively high intensity of the employed stressors, which limits applications in patients and longitudinal study designs. Here, we introduce a less intense neuroimaging stress paradigm in which subjects anticipate, prepare, and give speeches under simulated social evaluation without harsh investigator feedback or provoked performance failures (IMaging Paradigm for Evaluative Social Stress, IMPRESS). We show that IMPRESS significantly increases perceived arousal as well as adrenergic (heart rate, pupil diameter, and blood pressure) and hormonal (cortisol) responses. Amygdala and perigenual anterior cingulate cortex (pACC), two key regions of the emotion and stress regulatory circuitry, are significantly engaged by IMPRESS. We further report associations of amygdala and pACC responses with measures of adrenergic arousal (heart rate, pupil diameter) and social environmental risk factors (adverse childhood experiences, urban living). Our data indicate that IMPRESS induces benchmark psychological and endocrinological responses to social evaluative stress, taps into core neural circuits related to stress processing and mental health risk, and is promising for application in mental illness and in longitudinal study designs.